(untitled) (Islas, 2022)
Introduction: This article, derived from a diploma work, is an approach to a less studied part of a Roberto Fernández Retamar’s literary work: his poetry. Methods: It has been used for poetic analysis to cover both the formal elements in the composition of the poems, as well as their content, depending on the rhetorical and discursive resources of the author in his works. Results: From the formal point of view, his poetry maintains the codes of conversational poetry: tendency to prosaism and the anecdotal, metrical, strophic and rhyming freedom, accentual variety, combination of verses of major and minor art, which provides him with inner rhythm Metaphor, antithesis and repetitions are recurrent rhetorical figures; his lyric is based on expressive simplicity, clarity and the use of sometimes antipoetic terms to achieve a fast, effective and unadorned communication. Conclusions: The analysis of his poetic trajectory reveals the author´s commitment to the historical circumstances and to his inner world, expressed in the conjunction of the epic and the solidity of his ethical and political convictions, in the apprehension of the every.